Interleukin-1 Ligands and Receptors in Lumpfish (Cyclopterus lumpus L.): Molecular Characterization, Phylogeny, Gene Expression, and Transcriptome Analyses - Eggestøl, Håvard Ø.; Lunde, Harald S.; Knutsen, Tim Martin; Haugland, Gyri T. (Frontiers in Immunology, 2020)
The interleukin (IL)-1 family play a fundamental role as immune system modulators. Our previous transcriptome-analyses of leukocytes from lumpfish (Cyclopterus lumpus L.) showed that IL-1β was among the most highly upregulated genes following bacterial exposure. In the present study, we characterized IL-1 signaling pathways, identified and characterized four ligands of the IL-1 family in lumpfish; IL-1β type I and type II, IL-18 and the novel IL-1 family members (nIL-1F), both at mRNA and gene levels. The two IL-1β in lumpfish is termed IL-1β1 (type II) and IL-1β2 (type I). Furthermore, a comprehensive phylogenetic analysis of 277 IL-1 ligands showed that nIL-1F, in common with IL-1β, likely represents an ancestral gene, as representatives for nIL-1F were found in cartilaginous and lobe-finned fish, in addition to teleosts. This shows that nIL-1F is not exclusively present in teleosts as previously suggested. Our analyses of exon-intron structures, intron phases, phylogeny and synteny clearly show the separation of IL-1β into groups; type I and type II, which likely is a result of the third whole genome duplication (3R WGD).The phylogenetic analysis shows that most teleosts have both type I and type II. Furthermore, we have determined transcription levels of the IL-1 ligands in leukocytes and 16 different tissues, and their responses upon in vitro stimulation with seven different ligands. In addition, we have identified the IL-1 receptors IL-1R1, IL-1R2, IL-1R4 (ST2/IL-33 receptor/IL-1RL), IL-1R5 (IL-18R1) and partial sequences of DIGIRR and IL-1R3 (IL-RAcP). Identification of immune molecules and description of innate responses in lumpfish is interesting for comparative and evolutionary studies and our study constitutes a solid basis for further functional analyses of IL-1 ligands and receptors in lumpfish. Furthermore, since lumpfish are now farmed in large numbers to be used as cleaner fish for removal of sea lice on farmed salmon, in-depth knowledge of key immune molecules, signaling pathways and innate immune responses is needed, as the basis for design of efficient immune prophylactic measures such as vaccination.